MENARA KUDUS: IS IT A MINARET OR A TEMPLE? A STUDY OF ARCHITECTURAL ACCULTURATION - ashadi, ashadi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Menara Kudus is a minaret building property of an old mosque in Kudus city, Indonesia. The shape of the minaret building is unique and different from the shape of the mosque minarets in general, both in Indonesia and in the Islamic world; The shape of the building is more similar to a Hindu / Buddhist temple building in Java. This paper aims to find answers to questions raised by some scientists about the status of the Menara Kudus building; Is it a temple building that has changed its function, or is it a mosque minaret building. How is the architectural acculturation of the Menara Kudus building? The method used was comparative descriptive to describe the Menara Kudus, the Hindu / Buddhist temples, and the minaret of the old mosque. The comparative method compares the Menara Kudus building with the temple and the mosque minaret to get similarities and differences. The result is that the Menara Kudus is thought to be a temple building that has changed its function. There has been architectural acculturation, a mixture of local and non-local elements.